Proposing a Zakat Empowerment Program Using IDZ: Case from Cemplang Village, Bogor, Indonesia - Khairunnajah Khairunnajah; Irfan Syauqi Beik; Bagus Sartono (International Journal of Zakat, 2019)
Zakat has enormous potential for the development of a nation. Recently, The Ministry of Village, Development of Disadvantaged Areas and Transmigration targets to eradicate 5000 poor villages. However, the current number of underdeveloped villages is still high. For this, the empowerment program of BAZNAS can integrate with the local government to participate in the development of backward regions. Zakat Community Development is one of BAZNAS subsidiary aiming at community development. This study engages the index of zakat village (IDZ) to investigate the feasibility of Cemplang village in getting assisted by BAZNAS empowerment programs. This study finds that the Village is considered to get supported by zakat funds. Keywords: zakat, community development, empowerment, IDZ